The Natural Characteristics of the Qalatubzan Valley in the Formation of the Basin and the Runoff - Al-Fayadi, Ranya; AlIbrahimi, Suhaila (Al-Adab Journal, 2023)
The study aims to identify the natural characteristics of the Qalatubzan Valley in the formation of the basin and the runoff in it. It also aims to provide a picture of the nature of the Qalatubzan Valley Basin in soil degradation and erosion, and to reveal the nature of this effect using remote sensing (RS) and geographic information systems (GIS) techniques to know the impact of erosion. Most of the geological formations that make up the surface of the study area in the northeastern parts were subjected to erosion and water erosion, and canyons and river valleys were formed. This reflects the efficiency of water erosion processes over time or through geological time. Geographically, the Qalatubzan Valley Basin is located in the Kalar district of the Sulaymaniyah Governorate, between two latitudes (35° 4ʹ 56ʹʹ _25ʹ 53° 34) to the north. And longitudes (45° 35ʹ 6ʹʹ- 53ʹ 21° 45) east, with an area of ​​(149,476 km2). The area is administratively defined from the north and northwest by Kalar District, from the east by Darbandikhan District, and from the south by Khanaqin District and Diyala River. The Qalatubzan Valley Basin is one of the important basins in the Sulaymaniyah Governorate due to its agricultural importance.